2019
DOI: 10.1098/rsos.190211
|View full text |Cite
|
Sign up to set email alerts
|

Agarwood wound locations provide insight into the association between fungal diversity and volatile compounds in Aquilaria sinensis

Abstract: The aim of the present study was to investigate the effect of wound location on the fungal communities and volatile distribution of agarwood in Aquilaria sinensis . Two-dimensional gas chromatography with high-resolution time-of-flight mass spectrometry revealed 60 compounds from the NIST library, including 25 sesquiterpenes, seven monoterpenes, two diterpenes, nine aromatics, nine alkanes and eight others. Of five agarwood types, Types IV and II contained the greatest number and concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Agarwood is a resinous and fragrant wood that is an essential ingredient of some exclusive perfumes and is extensively used as medicine and incense across Asia, the Middle East, and Europe ( 3 , 4 ). The annual global agarwood market is valued at 6 to 8 billion USD, not including the proportion of unrecorded trade ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Agarwood is a resinous and fragrant wood that is an essential ingredient of some exclusive perfumes and is extensively used as medicine and incense across Asia, the Middle East, and Europe ( 3 , 4 ). The annual global agarwood market is valued at 6 to 8 billion USD, not including the proportion of unrecorded trade ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…The dimeric 2-(2-phenylethyl) chromones of agarwood lead to the identification by structure. Liu et al [27] isolated different kinds of 2-(2-phenylethyl) chromones from agarwood. Mei et al [28] analyzed the extracts by GC-MS after extracting high-quality agarwood with ether, and found that the relative content of 2-(2-phenylethyl) chromone compounds was 60% in high-quality agarwood.…”
Section: Chromonesmentioning
confidence: 99%
“…A key fragrance raw material and essential oils have many applications and may possess biochemical activity. Among the GC×GC applications on plant essential oils and volatiles, a highlighted topic was the analysis of woody-scented , essential oils and fragrance ingredients, such as agarwood, guaiacwood, and vetiveryl acetate.…”
Section: Applicationsmentioning
confidence: 99%
“…Agarwood composition was investigated in two works , using GC×GC. A three-dimensional approach (GC–GC×GC) was used by Yan et al to resolve oxygenated sesquiterpenes of this oleoresin, in which the system configuration was described previously (Higher Dimension Separation section).…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation